Facilitated endospore detection for Bacillus spp. through automated algorithm‐based image processing. Issue 3 (10th December 2021) - Biermann, Riekje; Niemeyer, Laura; Rösner, Laura; Ude, Christian; Lindner, Patrick; Bice, Ismet; Beutel, Sascha
Abstract: Bacillus spp. endospores are important dormant cell forms and are distributed widely in environmental samples. While these endospores can have important industrial value (e.g. use in animal feed as probiotics), they can also be pathogenic for humans and animals, emphasizing the need for effective endospore detection. Standard spore detection by colony forming units (CFU) is time‐consuming, elaborate and prone to error. Manual spore detection by spore count in cell counting chambers via phase‐contrast microscopy is less time‐consuming. However, it requires a trained person to conduct. Thus, the development of a facilitated spore detection tool is necessary. This work presents two alternative quantification methods: first, a colorimetric assay for detecting the biomarker dipicolinic acid (DPA) adapted to modern needs and applied for Bacillus spp. and second, a model‐based automated spore detection algorithm for spore count in phase‐contrast microscopic pictures. This automated spore count tool advances manual spore detection in cell counting chambers, and does not require human overview after sample preparation. In conclusion, this developed model detected various Bacillus spp. endospores with a correctness of 85–89%, and allows an automation and time‐saving of Bacillus endospore detection. In the laboratory routine, endospore detection and counting was achieved within 5–10 min, compared to up to 48 h with conventional methods. The DPA‐assay on the other hand enabled very accurate spore detection by simple colorimetric measurement and can thus be applied as a reference method.